Electrochemical sensing strategies for on‐site testing of pathogenic nucleic acids - Yusuke Kanno; Shuzo Masui; Yusuke Ota; Ryoichi Saito; Takasi Nisisako (Electrochemical Science Advances)
Abstract Rapid and reliable on‐site pathogen testing is crucial for diagnosing and managing human health. Nucleic acids (NAs) containing genetic information are valuable target molecules for pathogen testing, and sensitive and rapid detection of NAs using electrochemical approaches has been intensively investigated. Detection approaches for NAs are diverse and compatible with current gene amplification methods and continue to expand with the development of novel functional materials and molecules. The variety of electrochemical sensing devices also continues to expand, and more practical testing is being pursued. This review outlines the latest detection approaches and basic guidelines for NA detection. Furthermore, this review provides an overview of electrochemical sensing devices that utilize novel and unique materials and functions and comprehensively discusses their advantages.